Traditional and indigenous fruits and vegetables for food system transformation - Kennedy, Gina; Kanter, Rebecca; Chotiboriboon, Sinee; Covic, Namukolo; Delormier, Treena; Longvah, Thingnganing; Maundu, Patrick; Omidvar, Nasrin; Vish, Prakash; Kuhnlein, Harriet (Oxford University Press, 2021)
Fruit and vegetable consumption is recommended in numerous food-based dietary guidelines and forms a key recommendation in many international statements related to healthy diets. There are thousands of fruit and vegetable species from which to choose, but despite this abundance from nature, populations in most countries neither produce nor consume the recommended daily amounts of fruits and vegetables. There is enormous potential to better incorporate the wealth of diverse fruit and vegetable species and varieties into food systems. Known and preserved by indigenous communities, these hidden food treasures can foster collaborative research and learning. This perspective from the Task Force on Traditional and Indigenous Food Systems and Nutrition of the International Union of Nutritional Sciences (IUNS) highlights 5 key actions that can be taken by individuals, communities, and nations to reshape dialogue about traditional and indigenous fruits and vegetables to benefit people and planetary ecosystems.